Increased expression of the gene for the pro alpha 1(IV) chain of basement-membrane procollagen in cultured skin fibroblasts from two variants of osteogenesis imperfecta. - Pihlajaniemi, T (1989)
Fibroblasts from two lethal variants of osteogenesis imperfecta were shown to synthesize increased amounts of type IV procollagen. Previous studies established that one of these variants had a non-functional allele for the pro alpha 2 chain of type I procollagen, whereas the other pro alpha 2(I) allele contained a mutation leading to synthesis of shortened pro alpha 2(I) chains. In the two variants, the relative level of mRNA for pro alpha 1(IV) was 31 and 42% of the level of mRNA for pro alpha 1(I) chains. A value of less than 2% was found for a third lethal and four non-lethal variants of osteogenesis imperfecta. Immunofluorescent staining of fibroblasts from the two variants synthesizing increased amounts of type IV procollagen indicated that a homogeneous population of cells synthesized both type IV and type I procollagen. The results suggest that mutations in the type I procollagen genes that result in osteogenesis imperfecta can be associated with increased expression of the genes for type IV procollagen.